Diatom flora of Hasina pond, Morang, Nepal - Rai, Shiva Kumar; Adhikari, Kapindra (Nepalese Journal of Biosciences, 2019)
Epiphytic diatoms of Hasina pond were studied during winter, summer, and monson seasons in 2014-2015. Samples were collected by squeezing submerged roots and leaves of hydrophytes and frustules were cleaned using nitric acid. A total 59 diatoms under 27 genera and 19 families were reported among which 33 diatoms were new to the country. Epithemia adnata, Rhopalodia gibba, Gomphonema truncatum, Nitzschia palea, Ulnaria acus, U. ulna and Pinnularia amabilis were dominant in the pond. Diatom species were found maximum in summer (40%) and minimum in monsoon (28%) seasons.